Representaciones y estereotipos de la masculinidad en el cine boliviano contemporáneo - Pablo Virguetti (Les Cahiers ALHIM)
In this work I expose an analysis of the different discourses and imaginaries of masculinity that appear in Bolivian contemporary cinema. Specially, my study focuses in two films, Rodrigo Bellot’s Dependencia sexual and Juan Carlos Valdivia’s Zona Sur. I posit that there is a prevailing masculinity expression, virility, which comes from a social construction that drives men to a situation of constantly doing the effort of showing power. Nevertheless, the study also highlights other ways in which different versions of masculinity are shown and their typical issues. Finally, this work tries to adopt a structural look of masculinity imaginaries, these being a determining tool to negotiate within social contract.